If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 6 + -11 = 4x + 3 Reorder the terms: 6 + -11 + 5x = 4x + 3 Combine like terms: 6 + -11 = -5 -5 + 5x = 4x + 3 Reorder the terms: -5 + 5x = 3 + 4x Solving -5 + 5x = 3 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -5 + 5x + -4x = 3 + 4x + -4x Combine like terms: 5x + -4x = 1x -5 + 1x = 3 + 4x + -4x Combine like terms: 4x + -4x = 0 -5 + 1x = 3 + 0 -5 + 1x = 3 Add '5' to each side of the equation. -5 + 5 + 1x = 3 + 5 Combine like terms: -5 + 5 = 0 0 + 1x = 3 + 5 1x = 3 + 5 Combine like terms: 3 + 5 = 8 1x = 8 Divide each side by '1'. x = 8 Simplifying x = 8
| 4/3(3.14)(9)E3 | | -6x-4(-6x-3)=257 | | 260-2/3 | | 4x-1=120 | | 6x+4-2x=16 | | -4(5-w)-(4w-8)=-12 | | -4(5-6)-(4w-8)=-12 | | -8+4v=12 | | 4/3(3.14)(3)E3 | | 8(x-2)=4y | | 4x+20=7x-25 | | -2(p-2)=-2(1-2p) | | -14-z/9=-12 | | 2(10+x)=90 | | 31=6+12+c | | 10x+1-2x=3+8x-10 | | -11=-5(3k+8)+8(-5-k) | | 4(2x-3)=x+9 | | -6(-6n+7)-7=-157 | | 12x-1=-7 | | 3-4(x-3)=3(x-6)-7x | | -21w+5+4w-1= | | 6(-4-x)=-18x | | 0.4x+3=-0.2x-0.6 | | 5x+5=3x+4+2x+1 | | x^2+bx+6.25=0 | | 90=2x+10 | | X+y=122 | | -3(4+3)=2y+3 | | 17-3=4x | | -3(q-7)=2+q-21 | | 2x+1=2(x-4) |